The Effectiveness of Limited Face-to-Face Learning in Improving Student Learning Motivation during the Covid-19 Pandemic - Deflita Rusly Norsly Lumi; Febri Kurnia Manoppo; Berdinata Massang (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to find out the motivations of learning students of the Faculty of Christian Education who follow limited face-to-face learning. This research uses quantitative research methods with a form of true experimental design, namely Posttest-Only Control Design. The population in the study was 329 students in semester 1 and semester 3 at the Faculty of Christian Education, which was divided into experimental classes and control classes. Calculation of sample numbers using Issac and Michael formulas, sample numbers in the experimental class of 128 students, and control classes of 103 students were randomly selected. The research instrument uses a questionnaire, consisting of 26 items developed based on Marx and Tombuch's theory of motivation to study. Data is shared with students online through the Google Form platform. The data that has been collected is statistically tested: the normality test, the homogeneity test, and the Mann-Whitney U-test test. The results showed that the Value of the Mann-Whitney U-test was 4849.500, and the signification value was 0.001, which is less than 0.05 (P 0.05). The results show that there are differences in the learning motivation of students who take part in limited face-to-face lectures, whereas students who take limited face-to-face lectures have higher motivation.